A Five-Year Review of Adverse Cutaneous Drug Reaction in a Tertiary Care Hospital in Yogyakarta, Indonesia - Dyah Ayu Mira Oktarina; Maria Sophiati; Erinda Maharani Rambu Moha; Fajar Waskito; Hardyanto Soebono (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: The prevalence of adverse drug reactions is likely to increase, and it is associated with increased usage of various drugs. Adverse Cutaneous Drug Reaction (ACDR) is the most frequent adverse drug reaction (30–45%). In Indonesia, the study on the prevalence of ACDR is still limited. Purpose: This study investigated the prevalence, clinical features, causative agents, and mortality rate of ACDR with a type-IV hypersensitivity reaction among patients attending the Department of Dermatology and Venereology in Dr. Sardjito Hospital, Yogyakarta. Methods: This retrospective study was conducted examining medical records undertaken for five years (2011–2015). Of 68,375 patients medicated in the Department of Dermatology and Venereology, 397 patients were diagnosed as ACDR with a type-IV hypersensitivity reaction. Detailed history, including age, sex, past history, and family history of drug reaction taken by the patient, were obtained. Patch testing was done wherever feasible. Result: Of 68,375 patients, 397 patients were included in ACDR with type-IV hypersensitivity (0.58%), giving a 5% of mortality rate. The mean age of the patients was 40.42 years (±16.30; range 18 to 89 years). The female to male ratio was 1.1: 1. The Maculopapular rash was the most common ACDR manifestation (50.88%), followed by Stevens-Johnson Syndrome (13.85%), Fixed Drug Eruption (12.85%), and Drug Reaction with Eosinophilia and Systemic Symptoms (10.08%). The most common causative agents were beta-lactam (16.55%), NSAIDs (12.18%), and acetaminophen (8.62%). Conclusion:  Prescription of those drugs should be considered carefully so the incidence of ACDR can be reduced.